2020
DOI: 10.1016/j.eja.2020.126130
|View full text |Cite
|
Sign up to set email alerts
|

Root to shoot and carbon to nitrogen ratios of maize and soybean crops in the US Midwest

Abstract: Root traits are important to crop functioning, yet there is little information about how root traits vary with shoot traits. Using a standardized protocol, we collected 160 soil cores (0−210 cm) across 10 locations, three years and multiple cropping systems (crops x management practices) in Iowa, USA. Maximum root biomass ranged from 1.2 to 2.8 Mg ha−1 in maize and 0.86 to 1.93 Mg ha−1 in soybean. The root:shoot (R:S) ratio ranged from 0.04 to 0.13 in maize and 0.09 to 0.26 in soybean. Maize produced 27 % more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 76 publications
(105 reference statements)
6
27
1
Order By: Relevance
“…Deep soil cores were collected in the plant row during the mid-grain filling period (a period when root mass is maximum) ( 91 ) using a 6.2-cm-diameter Giddings probe. One soil core was collected in each of three plots that were arranged in randomized block design.…”
Section: Methodsmentioning
confidence: 99%
“…Deep soil cores were collected in the plant row during the mid-grain filling period (a period when root mass is maximum) ( 91 ) using a 6.2-cm-diameter Giddings probe. One soil core was collected in each of three plots that were arranged in randomized block design.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, on 6 maize varieties concomitantly evaluated in China and in the USA, Yu et al [74] found R/S ratios values ranging from 0.047 to 0.088, with a mean value of 0.08, identical to the value found in our study. In another study conducted in the US Midwest, R/S ranged from 0.04 to 0.13 for maize (Zea mays L.) and 0.09 to 0.26 for soybean (Glycine max L.) [73].…”
Section: Maize Root/shoot Ratiosmentioning
confidence: 99%
“…The R/S parameter represents the relative plant biomass allocated to plant tissues that have supportive functions (roots) to the amount of those (shoots) that have growth functions [71,73]. Among cereals, maize is characterized by high R/S values [67].…”
Section: Maize Root/shoot Ratiosmentioning
confidence: 99%
See 2 more Smart Citations